2009
DOI: 10.1186/ar2855
|View full text |Cite
|
Sign up to set email alerts
|

Insights in to the pathogenesis of axial spondyloarthropathy based on gene expression profiles

Abstract: IntroductionAxial spondyloarthropathy (SpA) is a group of inflammatory diseases, with ankylosing spondylitis as the prototype. SpA affects the axial skeleton, entheses, joints and, at times, the eyes. This study tested the hypothesis that SpA is characterized by a distinct pattern of gene expression in peripheral blood of affected individuals compared with healthy controls.MethodsHigh-density, human GeneChip® probe arrays were used to profile mRNA of peripheral blood cells from 18 subjects with SpA and 25 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 28 publications
(29 reference statements)
2
46
0
1
Order By: Relevance
“…Previous microarray studies in AS have generally not included sex-matched patients and controls, while those that balanced the sex of patients and controls did not independently analyze males and females (26)(27)(28)(29). These studies demonstrate mild hierarchal clustering of AS patients and controls, as in the current study, supporting the heterogeneity of the disease at the transcription level.…”
Section: Discussionsupporting
confidence: 63%
“…Previous microarray studies in AS have generally not included sex-matched patients and controls, while those that balanced the sex of patients and controls did not independently analyze males and females (26)(27)(28)(29). These studies demonstrate mild hierarchal clustering of AS patients and controls, as in the current study, supporting the heterogeneity of the disease at the transcription level.…”
Section: Discussionsupporting
confidence: 63%
“…139 A role for the innate system in AS has long been postulated due to the proposed link between an as yet unknown pathogen and disease onset. 140 SPARC, a bone matrix protein, was also upregulated in two of the studies 136,137 which suggests dysregulation of the bone matrix which might contribute to the joint ankylosis.…”
Section: Circulating Cell Studiesmentioning
confidence: 93%
“…Two kits have been specifically developed for transcriptomic studies in whole blood with the blood collected into an RNA preservative which stabilises the RNA allowing shipping/initial storage at room temperature with minimal degradation (PAXgene from Qiagen Three whole genome expression profiling studies have been published using whole blood in spondylarthropy all using the PAXgene technology. [135][136][137] Sharma et al compared healthy controls and spondyloarthropy patients but used a slightly unusual approach. Rather than analysing a main sample group by microarray then confirming candidate genes by qPCR in a second cohort, they split the sample groups into a discovery and a validation set and microarrayed both groups and compared differentially expressed genesets.…”
Section: Circulating Cell Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…64 Finally, a recent study also found a TREM-1 upregulation in peripheral blood cells from patients suffering from spondylarthropathy. 65 Thus, while TREM-1 role in acute inflammation, especially during sepsis, is today better understood, its function during chronic rheumatic diseases only begins to be elicited.…”
Section: Effects Of the Trem-1 Pathway Modulation During Inflammatorymentioning
confidence: 99%